Effectiveness of combined bangle rhizome (Zingiber montanum) and black betel leaf (Piper betle var. nigra) water extract in combatting caries-causing oral pathogens using response surface methodology - Masyhudi; Candra, Krishna Purnawan; Hardi, Esti Handayani; Ahmad, Islamuddin; Panggabean, Aman Sentosa; Kuncoro, Hadi; Nugroho, Rudy Agung (Agriculture and Natural Resources, 2025)
Importance of the work: The research benefit lies in the potential use of endemic herbal extracts to maintain dental and oral health. Objectives: To determine the optimal conditions for the combination of bangle and black betel extracts to inhibit dental caries pathogenic bacteria. Materials and Methods: Water extracts of bangle rhizomes (BR) and black betel leaves (BL) were utilized to identify the most effective formula for suppressing three dental pathogenic bacteria by employing response surface methodology. The factors investigated were the BR concentration, BL concentration, and the ratio of BR to BL. Results: A BR of 10–20% significantly affected the antibacterial activity against Enterococcus faecalis and Streptococcus mutans, whereas a BL of 10–20% had no significant effect on the growth zones of E. faecalis and S. mutans. The BR-BL combination (ratio 1:1–3:1) significantly influenced antibacterial activity in inhibiting the growth of both bacteria. Porphyromonas gingivalis was not affected by any treatment. The optimization of the combination of the three factors for the antibacterial activity against E. faecalis was achieved effectively under the conditions of BR 20.0%, BL 19.8%, and a BR-BL ratio of 3, whereas for S. mutans, it was BR 20.0%, BL 10.0 %, and a BR-BL ratio of 3. Main finding: The results suggest that BR alone is a promising natural ingredient for preventing oral infections against E. faecalis and S. mutants, but its combination with BL is necessary to improve its antibacterial effectiveness against E. faecalis.